Synergistic upconversion and molecular imprinting in flame-made Yb/Nd co-doped TiO2 for targeted photocatalytic degradation of tetracycline in complex water - Xinhao Meng; Shuohan Wu; Zhijun Yang; Heran Zhang; Zhengliang Bian; Dongliang Zhang; Shuning Xiao; Yanjie Hu; Ying Li; Wei Bi (Environmental Research, 2026)

Bridging zero-dimensional loss units with one-dimensional carbon nanotubes for gradient-laminated polyarylene ether nitrile composites toward absorption-enhanced electromagnetic interference shielding - Jiabin Hu; Yunfeng Guo; Yu Zheng; Ting Zhang; Shaoqian Zhou; Yani Chen; Mei Liu; Qian Xiao; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Microdomain contraction and crystalline refinement in polyarylether nitrile alloys for high-temperature dielectric stability - Ting Zhang; Hongbo Shen; Youbin Wan; Yani Chen; Qian Xiao; Shaoqian Zhou; Yunfeng Guo; Jiabin Hu; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Janus structured magnetic MOFs-polyarylether nitrile/MXene composite films with gradient interfaces for electromagnetic interference shielding and thermal management - Yunfeng Guo; Jiabin Hu; Xin Sun; Ting Zhang; Shaoqian Zhou; Liang He; Hongbo Shen; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

The Training Effect of Tactical Awareness and Technical-Tactical Performance Among Youth Football Players: A Systematic Reviews and Meta-analysis - Jiahui Hu; Yeqin Zhang; Shuning Liu; Danyang Li; Dingmeng Ren (Journal of Science in Sport and Exercise, 2026)

The Effect of Mining Activities on the Hydrochemical and Isotopic Characteristic of Groundwater in the Shennan Coal Mine, Shaanxi Province, Northwest China - Ankun Luo; Shuning Dong; Hao Wang; Shouchuan Zhang; Haidong Cao; Shidong Wang; Zhongkui Ji; Xiaoyu Hu (Mine Water and the Environment, 2026)

Interactions in starch-lipid complex systems improve 3D printing accuracy and form resistant starch structures: Based on complex properties and molecular simulations - Yanru Bao; Shu Ma; Shuning Yuan; Yu Hu; Tao Yang; Hao Jiang (Food Chemistry, 2025)

Differential Effects of Murine Stroke Models on Dopaminergic Neurons, Glial Responses, and Neurobehavioral Outcomes - Sidra Tabassum; Heng Hu; Silin Wu; Shuning Huang; Bosco Seong Kyu Yang; Chang-Hun Lee; Aaron W. Gusdon; Xuefang S. Ren (Translational Stroke Research, 2025)

Interplay between Nrf2 and ROS in regulating epithelial-mesenchymal transition: implications for cancer metastasis and therapy - Yi Xu; Shuning Hu; Rui Chen; Sheng Xu; Guangyang Yu; Lili Ji (Molecular Biology Reports, 2025)
Epithelial-mesenchymal transition (EMT), including developmental (Type I), wound healing (Type II), and pathological (Type III) subtypes, constitutes a critical driver of cancer metastasis. This review analyzes the redox interplay between nuclear factor erythroid 2-related factor 2 (Nrf2) and reactive oxygen species (ROS) in EMT regulation and cancer progression. Nrf2 maintains redox homeostasis through antioxidant gene activation while paradoxically promoting tumor survival and drug resistance via Keap1-dependent degradation and phosphorylation-mediated stabilization. ROS generated through mitochondrial and NADPH oxidase pathways exhibit dual functionality: moderate levels activate EMT transcription factors to drive metastasis and cancer stem cells (CSCs) plasticity, whereas excessive ROS induce apoptosis and ferroptosis. While Nrf2 typically suppresses EMT through ROS neutralization and epithelial integrity preservation, chronic Nrf2 activation in CSCs paradoxically sustains metastatic potential through redox buffering. This synthesis delineates the spatiotemporal regulation of Nrf2-ROS-EMT networks across tumor microenvironments, emphasizing therapeutic opportunities through redox balance modulation and pathway-specific Nrf2 inhibition in advanced malignancies.

Experimental investigation on the permeability evolution and mechanism of burnt rock under fluid–solid coupling conditions - Ankun Luo; Shuning Dong; Hao Wang; Xiaoming Guo; Zhongkui Ji; Tiantian Wang; Hongbo Shang; Xiaoyu Hu; Yuan Liang; Zhennan Zhu (Acta Geodaetica et Geophysica, 2025)

Matrix crystallinity and nanofiller compatibility optimization of polyarylether nitrile nanocomposite films for enhanced high-temperature energy storage - Ting Zhang; Yani Chen; Shaoqian Zhou; Jinqi Wu; Yunfeng Guo; Jiabin Hu; Qian Xiao; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2025)

Dopamine-functionalized chondroitin sulfate/gelatin-based composite hydrogels for enhancing wound healing and bone regeneration - Jian Yang; Jiale Jin; Haojie Yu; Yun Wang; Li Wang; Xiaowei Liu; Dongyu Wang; Yudi Huang; Chenguang Ouyang; Yu Wang; Yichuan Hong; Shuning Ren; et al. (Carbohydrate Polymers, 2025)

Establishment and application of a duplex fluorescent quantitative PCR assay for H9N2 subtype avian influenza virus and infectious bronchitis virus - Wanting Zhou; Qiuyan Mao; Shuning Zhou; Tingting Li; Jie Tian; Xiaoqi Li; Shuo Liu; Cheng Peng; Zhibin Hu; Jinping Li; Guangyu Hou; Houhui Song; et al. (Virus Genes, 2025)

Towering sustainability: Unraveling the complex effects of skyscrapers on urban resilience - Yihua Yu; Caili Yang; Qingsha Hu; Shuning Kong (Environmental Impact Assessment Review, 2024)

Utilization of γ-polyglutamic acid/pectin hydrogel with 1-MCP on the apricot storage - Shuning Yang; Jinfeng Zhang; Xiaopei Hu; Suhong Li; Tuoping Li (Journal of Stored Products Research, 2024)

Impact of long-term mining activity on groundwater dynamics in a mining district in Xinjiang coal Mine Base, Northwest China: insight from geochemical fingerprint and machine learning - Ankun Luo; Shuning Dong; Hao Wang; Zhongkui Ji; Tiantian Wang; Xiaoyu Hu; Chenyu Wang; Shen Qu; Shouchuan Zhang (Environmental Science and Pollution Research, 2024)